Program Indonesia 2045 dan Perlunya Moderasi Beragama di Kalangan Generasi-Z - Dewi Nurhaliza; Afiyatun Kholifah (Moral : Jurnal kajian Pendidikan Islam, 2025)
This article discusses the strategic role of general moderation of Generation Z in supporting the vision of "Golden Indonesia 2045", emphasizing the importance of religious moderation as the foundation of social stability, tolerance, and interfaith harmony. Generation Z, as a digital generation that grew up in the midst of globalization and technological disruption, has great potential in forming an inclusive and resilient society against the threat of radicalism and intolerance. This study uses a qualitative approach through a literature study to explore how Generation Z understands, evaluates, and internalizes moderate religious values in daily life. The results of the analysis show that religious and religious literacy is a crucial element in building balanced social and spiritual awareness among the younger generation. This article also identifies strategies that can be applied by Generation Z as a social fortress, including through strengthening the values of moderation in formal education, using social media wisely, and integrating the principle of moderation in public policy. The mainstreaming of religious moderation in various sectors of life is believed to be able to foster a tolerant, critical, and globally competitive generation. Thus, Generation Z is not only the successor of the nation, but also the main actor in realizing a just, harmonious, and civilized Indonesian society towards 2045.